Fatherlessness and marital anxiety: A qualitative exploration of psychological dynamics among young adult women in Padang, Indonesia - Abrar, Kharisma Wulan; Fitriana, Dewi; Arlotas, Rena Kinnara (Institut Agama Islam Negeri Langsa, 2025)
Fatherlessness, defined as the physical or psychological absence of a father figure, is a prevalent phenomenon with significant long-term psychological consequences. This qualitative case study investigates the underexplored link between fatherlessness and marital anxiety among early adult women in Padang, Indonesia, a context with strong traditional and patriarchal norms. Through in-depth interviews and thematic analysis of two purposively selected participants (aged 21 and 22), the study examines the subjective experience and psychological underpinnings of this anxiety. Findings reveal that marital anxiety is not a singular fear but a complex syndrome stemming from a disrupted father-daughter attachment, which fosters a profound and generalized distrust of men. This foundational trauma interacts with the participants’ critical consciousness of patriarchal inequalities within marriage, transforming anxiety into a form of ideological resistance against perceived systemic injustice. Furthermore, sociocultural pressures to marry and constant exposure to negative marital narratives exacerbate this distress. A key insight is the identification of a distinct relational pathway leading to marital avoidance, contrasting with other documented responses to paternal absence. The study concludes that for these women, marital anxiety represents a meaningful, adaptive response to personal trauma and structural inequity. These findings underscore the need for support frameworks that address both attachment wounds and sociocultural critiques, offering a nuanced perspective for clinicians and researchers working on intergenerational trauma and gender-based psychological distress.